2016
DOI: 10.1007/s40266-016-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pharmacokinetic and Pharmacodynamic Properties Between Faster-Acting Insulin Aspart and Insulin Aspart in Elderly Subjects with Type 1 Diabetes Mellitus

Abstract: BackgroundDue to population aging, an increasing number of elderly patients with diabetes use insulin. It is therefore important to investigate the characteristics of new insulins in this population. Faster-acting insulin aspart (faster aspart) is insulin aspart (IAsp) in a new formulation with faster absorption. This study investigated the pharmacological properties of faster aspart in elderly subjects with type 1 diabetes mellitus (T1DM).MethodsIn a randomised, double-blind, two-period crossover trial, 30 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
7
25
0
4
Order By: Relevance
“…Cmax , onset of action and t Early 50% GIRmax for faster aspart in the present study in people with T2D are similar to those seen in people with T1D. 5,6,15 This indicates that the pharmacological characteristics of faster aspart immediately after dose administration are independent of type of diabetes.…”
Section: Safetysupporting
confidence: 77%
See 2 more Smart Citations
“…Cmax , onset of action and t Early 50% GIRmax for faster aspart in the present study in people with T2D are similar to those seen in people with T1D. 5,6,15 This indicates that the pharmacological characteristics of faster aspart immediately after dose administration are independent of type of diabetes.…”
Section: Safetysupporting
confidence: 77%
“…The majority of AEs were mild in intensity and assessed as unlikely to be related to T A B L E 1 Onset of exposure and onset of glucose-lowering effect for fast-acting insulin aspart versus insulin aspart in people with type 2 diabetes The overall left-shift of the pharmacokinetic/pharmacodynamic profiles with faster aspart versus IAsp in the present study in participants with T2D was comparable to that seen in people with T1D. 5,6,15 It has been reported that the absorption kinetics of human insulin are slower in people with T2D than in those with T1D 10,16 ; therefore, it is interesting that absolute values for onset of appearance, t Early 50%…”
Section: Safetymentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, offset of exposure and glucose‐lowering effect occurred 12–14 minutes earlier with faster aspart than with IAsp. Similar pharmacological properties following subcutaneous injection have been observed in elderly adults and in a Japanese population, as well as in children and adolescents with T1D …”
Section: Introductionsupporting
confidence: 76%
“…Development of novel insulin analogs with more rapid onset of activity and shorter duration of action (relative to current insulin analog products Humalog ® , Novolog ® , and Apidra ® (40-42)) could improve closed-loop systems by providing more predicable pharmacodynamic profiles and hence more accurate calculation of insulin doses. Examples of more rapid formulations are provided by Novolog-based FIAsp (a reformulation of insulin aspart to contain excepients that promote capillary absorption) or addition of the degradative enzyme hyaluronidase to wild-type insulin (rHuPH20; Halozyme, Inc.) (43, 44*, 45*); the latter approach is no longer being pursued.…”
Section: Mechanical Grismentioning
confidence: 99%